Filtrate reducer as well as preparation method and application thereof

By combining specific ternary polymers with nanomaterials, forming frozen gels, pulverizing and drying, the obtained filter reduction loss loss agent is ≤20mL after hot rolling at 220°C for 16 hours, which solves the problem of the failure of the existing filter reduction loss agent in ultra-high temperature deep well reservoirs, and achieves excellent high-temperature and high-salt resistance.

CN119912914APending Publication Date: 2025-05-02CHINA NAT PETROLEUM CORP

Patent Information

Application Number
CN202311432040.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing filter reduction agents are difficult to meet the needs of ultra-high temperature deep well reservoirs, and polymer molecular chains are prone to fracture and fail under high temperature conditions.

Method used

By combining a specific terpolymer with nanomaterials, the nanomaterials are polymerized by polymerizing 2-acrylamide-2-methylpropanesulfonic acid, acrylamide and sodium styrenesulfonate, and the nanomaterial is introduced into the polymer, forming a frozen gel and pulverizing and drying, to obtain a filter reduction agent with excellent resistance to high temperature and high salt.

Benefits of technology

After 16 hours of hot rolling aging at 220°C, the medium pressure filtration loss was ≤20mL, which significantly improved the high-temperature and high-salt resistance of the filter reduction loss agent, met the demand for ultra-high-temperature deep well reservoirs, and reduced the impact on the rheology performance of high-temperature high-density drilling fluid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004523935960000151
    Figure BDA0004523935960000151
Patent Text Reader

Abstract

The invention provides a preparation method of a filtrate reducer, which comprises the following steps: adjusting a 2-acrylamido-2-methylpropanesulfonic acid solution to be neutral, mixing the 2-acrylamido-2-methylpropanesulfonic acid solution with acrylamide and sodium p-styrenesulfonate, and then carrying out polymerization reaction in an oxygen-free atmosphere under the action of an initiator to obtain a polymer; and adding the uniformly dispersed nano material suspension into the polymer, aging to form jelly, crushing, drying, washing, drying again, and crushing again to obtain the filtrate reducer. According to the invention, the nanometer material and the specific ternary polymer are mixed and aged, and the dosage of each polymeric monomer and the nanometer material is limited, so that the finally obtained filtrate reducer is subjected to hot rolling aging at 220 DEG C for 16 hours under the conditions of ultrahigh temperature and high salt, and the medium-pressure filter loss is less than or equal to 20 mL.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of petroleum exploitation and oilfield chemical materials, and in particular to a fluid loss reducer and a preparation method and application thereof. Background Art

[0002] In recent years, the consumption of domestic oil and gas resources has increased rapidly, and oil and gas exploration and development has continued to develop from shallow to deep formations, and from conventional oil and gas to unconventional oil and gas. The geological conditions of deep and unconventional oil and gas formations are complex, and most of them face extreme environments such as high temperature, high pressure, and high salt. Drilling fluids are prone to performance degradation such as decreased viscosity and increased filtration, and even cause accidents such as well wall instability and collapse, which seriously affect drilling efficiency. Therefore, high-quality drilling fluid technology is the key to ensuring safe and efficient drilling.

[0003] As one of the core materials with the largest sales volume and the most extensive research in drilling fluid treatment agents, fluid loss reducers combine with clay particles through adsorption and hydration to form a stable spatial network structure, forming a dense low-permeability mud cake on the well wall, significantly reducing the risk of drilling fluid filtrate invading the formation and excessive filtration resulting in difficulty in pumping circulating fluids and well wall instability. The temperature and salt resistance of fluid loss reducers is the key to ensuring the stability of water-based drilling fluid performance in saline formations during high-temperature deep well drilling. In recent years, it has become a hot spot in the research of water-based drilling fluid technology at home and abroad, and has been valued by relevant domestic scientific researchers and manufacturers. At present, there are many types of temperature-resistant and salt-resistant fluid loss reducers, but there is a lack of in-depth understanding of the relationship between their main components, molecular structure and temperature and salt resistance, which also affects the in-depth research of temperature-resistant and salt-resistant fluid loss reducers, and the existing fluid loss reducers cannot meet the needs of ultra-high temperature deep wells.

[0004] Water-based drilling fluid fluid loss reducers widely used at home and abroad are divided into three categories according to their main components: natural polymer materials, polymers, and organic / inorganic composite materials. Among them, chemical modification of natural polymer materials can effectively improve the temperature and salt resistance of natural polymer materials and improve the fluid loss reduction performance. At present, natural polymer material fluid loss reducers mainly include three categories: starch, cellulose, and humic acid. Although there are many modification methods for starch and cellulose materials, which improve the temperature and salt resistance on the basis of raw materials, the performance improvement is limited, especially the temperature resistance is insufficient, generally below 180°C, which is difficult to meet the needs of deep well drilling. Polymer fluid loss reducers are mainly vinyl polymers. This type of fluid loss reducer usually uses acrylamide (AM) and a variety of functional monomers as raw materials, and is a mono- or poly-polymer formed by copolymerization; polymer fluid loss reducers mainly include linear polymer fluid loss reducers, branched polymer fluid loss reducers, and micro-cross-linked polymer fluid loss reducers according to the molecular spatial geometric configuration. However, polymer-based fluid loss reducers are prone to failure between polymer molecular chains and between polymers and clay under high temperature and high salt conditions. Inorganic / organic composite materials are materials prepared by blending and copolymerizing inorganic materials with polymers, in which the inorganic materials can be used as fillers or polymer monomers to interact with polymers to achieve a significant improvement in the overall material performance. The inorganic materials used in inorganic / organic composite materials are mostly highly heat-resistant and highly rigid substances. On the one hand, they can improve the overall temperature resistance of the composite materials, and on the other hand, they can effectively improve the temperature and salt resistance by increasing the molecular rigidity. At the same time, the use of organic / inorganic composite material fluid loss reducers can alleviate the environmental pollution problems caused by the large-scale use of polymers to a certain extent. Therefore, at present, temperature-resistant and salt-resistant organic / inorganic composite materials have become one of the important research directions for the development of drilling fluid fluid loss reducers.

[0005] For example, Chinese patent document CN109554170B discloses a calcium-resistant and high-temperature-resistant drilling fluid loss reducer and its preparation method, wherein a calcium-resistant and high-temperature-resistant drilling fluid loss reducer is prepared by quaternary copolymerization of vinyl sulfonic acid monomer, acrylamide, maleamic acid monomer and cationic vinyl monomer, which has a good protective effect on clay particles under high calcium ion concentration conditions, can form a low permeability, flexible, thin and dense filter cake, reduce the filtration loss of drilling fluid containing high calcium ions, and can be used in high calcium salt drilling fluid systems up to 150°C. However, the calcium-resistant and high-temperature-resistant drilling fluid loss reducer does not meet the requirements of ultra-high temperature deep wells. After hot rolling aging at 150°C for 16 hours, the medium pressure filtration loss reaches 206mL.

[0006] Zhao Kaiqiang et al. published the preparation and evaluation of high temperature and salt resistant starch graft copolymers [J]. Fine Petrochemicals, 2022, 39(06): 4-9, which disclosed the use of graft polymerization to graft acrylamide and KGM zwitterionic monomers into the starch skeleton to obtain a modified starch fluid loss agent. The optimal synthesis conditions are: m(starch): m(acrylamide): m(KGM zwitterionic monomer) is 3:5:2, the initiator addition is 0.9%, and the reaction temperature is 65°C. The modified starch fluid loss agent has good salt and calcium resistance and is resistant to temperatures up to 200°C: after aging at 200°C for 16h, the medium pressure fluid loss is ≤15mL. However, the modified starch fluid loss agent still cannot meet the needs of high temperature deep wells. When the temperature exceeds 200°C, the polymer molecular chains and the polymer and clay fail.

[0007] Chinese patent document CN108424754B discloses a high temperature and calcium salt resistant drilling fluid and its preparation method, specifically, a high temperature and calcium salt resistant drilling fluid fluid loss reducer is invented by using N-vinyl formamide, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid as monomers through ternary copolymerization. However, the high temperature and calcium salt resistant drilling fluid is aged at 150°C for 16 hours, and the high temperature and high pressure fluid loss reaches 84mL.

[0008] Chinese patent document CN108467713A discloses a method for preparing a low viscosity copolymer fluid loss reducer for drilling fluid. The preparation method comprises the following steps: step 1) weighing the following weight proportion: 0.2-1 part of initiator, 1-4 parts of 2-acrylamido-2-methylpropanesulfonic acid, 6-12 parts of acrylamide, 1-3 parts of sodium styrene sulfonate, and 0.5-2 parts of itaconic acid for standby use; step 2) dissolving the polymer monomers in the weight proportion of step 1) in distilled water, then adding 0.5-2 parts of nanomaterials by weight, stirring evenly, adjusting the pH to 5-10 with sodium hydroxide aqueous solution, adding distilled water to adjust the mass percentage concentration of the system to 20-40%, and obtaining a mixed solution; step 3) at 50-90° C., after passing nitrogen for 30 minutes, adding 0.2-1 parts of initiator by weight, reacting for 1-10 hours, and obtaining a polymer solution with good fluidity; step 4) spray drying the obtained polymer solution to obtain a fluid loss reducer. The low viscosity copolymer fluid loss reducer for drilling fluid has low viscosity, salt resistance, calcium and magnesium resistance, and high temperature resistance, and has little effect on the rheology of the system; and has a good water loss reduction effect after aging at 150°C in the composite salt water slurry, thereby greatly improving the efficiency of drilling. After aging at 150°C for 16 hours, the fluid loss is 9.6mL, but the hydroxyl groups on the surface of the inorganic nanomaterial and the polar groups of the polymerized monomers adsorb each other, resulting in physical isolation between the polymerized monomers and a decrease in the molecular weight of the polymer. Therefore, it cannot meet the needs of ultra-high temperature deep well reservoirs.

[0009] In summary, the existing fluid loss reducers are difficult to meet the needs of ultra-high temperature deep well reservoirs. The molecular chains of most polymer fluid loss reducers begin to break at 220°C, and the polymer molecular chains and between polymers and clay are prone to failure. Summary of the invention

[0010] In view of this, the present invention provides a method for preparing a fluid loss reducer. The fluid loss reducer prepared by the method has excellent resistance to high temperature and high salt, can meet the needs of ultra-high temperature deep well oil reservoirs, and at the same time reduces the impact on the rheological properties of high temperature and high density drilling fluid.

[0011] To achieve the above object, the present invention provides a method for preparing a fluid loss reducer, comprising the following steps:

[0012] The 2-acrylamido-2-methylpropanesulfonic acid solution is adjusted to be neutral, and then mixed with acrylamide and sodium styrene sulfonate to obtain a mixed solution; and then the mixed solution is polymerized in an oxygen-free atmosphere and under the action of an initiator to obtain a polymer;

[0013] adding (preferably dropping) a uniformly dispersed nanomaterial suspension into the polymer, aging to form a gel, and then crushing, drying, washing, drying again, and crushing again to obtain the fluid loss reducer;

[0014] The molar ratio of the 2-acrylamide-2-methylpropane sulfonic acid to the acrylamide is 1:(4-8), the molar ratio of the 2-acrylamide-2-methylpropane sulfonic acid to the sodium styrene sulfonate is (2-3):1, and the molar ratio of the 2-acrylamide-2-methylpropane sulfonic acid to the nanomaterial is 1:(0.01-1).

[0015] The oxygen-free atmosphere can be achieved by conventional methods in the industry, such as introducing nitrogen into the mixed solution and bubbling to remove oxygen for 1 to 2 hours until there is no oxygen in the corresponding reaction container and the mixed solution.

[0016] Optionally, in the preparation method of the fluid loss reducer provided by the present invention, when used to adjust the 2-acrylamide-2-methylpropane sulfonic acid solution to neutrality (pH=6-8), the regulator used is not limited, as long as the 2-acrylamide-2-methylpropane sulfonic acid solution can be adjusted to neutrality, such as sodium hydroxide solution.

[0017] Optionally, in the preparation method of the fluid loss reducer provided by the present invention, the nano material is selected from any one of nano calcium carbonate, nano silicon dioxide, nano aluminum oxide, nano magnesium carbonate, nano zinc oxide and nano titanium oxide; preferably nano silicon dioxide.

[0018] Optionally, in the preparation method of the fluid loss reducer provided by the present invention, the initiator is selected from ammonium persulfate and / or potassium persulfate. The specific amount of the initiator is not limited, and the conventional amount in the industry can be used to initiate polymerization without causing implosion. The amount of the initiator recommended by the present invention is 0.25% to 0.35% of the total mass of all monomers (2-acrylamido-2-methylpropanesulfonic acid, acrylamide and sodium styrene sulfonate).

[0019] Optionally, in the preparation method of the fluid loss reducer provided by the present invention, the total mass concentration of all monomers (2-acrylamide-2-methylpropane sulfonic acid, acrylamide and sodium styrene sulfonate) in the mixed solution obtained by adjusting the 2-acrylamide-2-methylpropane sulfonic acid solution to neutral is 20wt% to 40wt%.

[0020] Optionally, in the preparation method of the fluid loss reducer provided by the present invention, the polymerization reaction temperature is 40 to 60° C. and the time is 4 to 6 hours.

[0021] Optionally, in the preparation method of the filtration reducer provided by the present invention, the uniformly dispersed nanomaterial suspension is prepared by placing the nanomaterial in deionized water and then uniformly dispersing the nanomaterial in the deionized water, such as by means of ultrasonic oscillation. The specific oscillation time is not limited, and the nanomaterial is uniformly dispersed.

[0022] Optionally, in the preparation method of the fluid loss reducer provided by the present invention, anhydrous ethanol or acetone is used for washing to remove unreacted polymerized monomers.

[0023] Optionally, in the preparation method of the fluid loss reducer provided by the present invention, the temperature of the uniformly dispersed nanomaterial suspension when added to the polymer is 40 to 60° C.;

[0024] The aging temperature is 60-70° C. and the aging time is 1-2 hours.

[0025] The present invention also provides a fluid loss reducer, which is prepared by the fluid loss reducer preparation method.

[0026] The present invention also provides a water-based drilling fluid, comprising a fluid loss reducer prepared by the fluid loss reducer preparation method, wherein the content of the fluid loss reducer is 1.5wt% to 4wt% based on the total mass of the water-based drilling fluid being 100%.

[0027] Optionally, in the water-based drilling fluid provided by the present invention, the water-based drilling fluid also includes bentonite, sodium chloride and sodium carbonate; preferably, based on the total mass of the water-based drilling fluid as 100%, the content of the bentonite is 2% to 6%, the content of the sodium chloride is 2% to 6%, and the content of the sodium carbonate is 1% to 3%.

[0028] The present invention also provides application of the water-based drilling fluid in oil and gas drilling.

[0029] Compared with the prior art, the effects of the present invention are as follows:

[0030] Beneficial effect 1: The preparation method of the filtration reducer provided by the present invention is to mix and age the nanomaterial with a specific ternary polymer, and to limit the amount of each polymerized monomer and the nanomaterial, etc., so that the filtration reducer finally obtained is hot-rolled aged at 220°C for 16 hours under ultra-high temperature and high salt conditions, and the medium-pressure filtration loss is ≤20mL. Specifically, the present invention first selects 2-acrylamide-2-methylpropanesulfonic acid (AMPS) containing sulfonic acid groups, acrylamide (AM) and sodium styrene sulfonate (SSS) to polymerize in a specific ratio to obtain a ternary polymer, and at the same time, long-chain side groups and rigid side groups are introduced into the main chain of the polymer, respectively, so that it has good high temperature and salt resistance, and the hydration layer caused by the hydration groups such as the sulfonic acid group hinders the aggregation of clay particles, effectively controlling the filtration loss of the drilling fluid. On this basis, nanomaterials are further introduced to cooperate with the ternary polymer, and the temperature resistance of the inorganic particles of the nanomaterials is utilized. On the one hand, the high temperature and high salt resistance of the fluid loss reducer is significantly improved. On the other hand, it can also produce strong adsorption force with polar groups such as benzene rings on the polymer molecules, thereby improving the stability of the polymer fluid loss reducer molecular chain, thereby improving the resistance to saturated salt and reducing the impact on the rheological properties of high-temperature and high-density drilling fluids.

[0031] Beneficial effect 2: The filtrate reducer prepared by the preparation method of the filtrate reducer provided by the present invention has excellent temperature resistance not only in saturated salt drilling fluid, but also in other conventional water-based drilling fluids or low-salt drilling fluids. DETAILED DESCRIPTION

[0032] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0033] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0034] Table 1 Source of raw materials

[0035] name Specification Manufacturer Acrylamide AR Aladdin Reagent Co., Ltd. 2-Acrylamido-2-methylpropanesulfonic acid AR Sinopharm Chemical Reagent Co., Ltd. Sodium hydroxide AR Sinopharm Chemical Reagent Co., Ltd. Sodium styrene sulfonate AR Aladdin Reagent Co., Ltd. Nano Silica AR Aladdin Reagent Co., Ltd. Anhydrous ethanol AR Aladdin Reagent Co., Ltd. Sodium Bentonite industry Lianxin Jinying Casting Co., Ltd. Sodium chloride AR Aladdin Reagent Co., Ltd. Sodium carbonate AR Aladdin Reagent Co., Ltd.

[0036] Example 1

[0037] This embodiment provides a drilling fluid, and the preparation method thereof is as follows:

[0038] Polymer: Place a magnetic stirring bar in a four-necked flask, connect a thermometer and a condenser, fix the four-necked flask in a constant temperature heating magnetic stirrer, then dissolve 50.7 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in 327 g of deionized water, and adjust the pH of the system to 8 with a NaOH solution, then add 72.4 g of acrylamide (AM) and 16.9 g of sodium styrene sulfonate (SSS), stir well, introduce nitrogen for bubbling and deoxygenation for 1 hour until there is no oxygen in the four-necked flask and the solution, start heating to 55°C, add 0.42 g of initiator (the molar ratio of ammonium persulfate to potassium persulfate is 1:1), and carry out polymerization reaction at 55°C for 5 hours to obtain a polymer.

[0039] Fluid loss reducer: 4.66 g of inorganic nano-silicon dioxide particles were added to 50 g of deionized water, and ultrasonically oscillated for 1 hour to obtain a uniformly dispersed nano-silicon dioxide suspension; then the suspension was added dropwise to the above-mentioned four-necked flask containing the polymer, and stirred at 55°C for 1 hour, then the stirring was stopped and the temperature was raised to 65°C for aging for 1 hour until it became a gel; then the gel was cut into pieces and dried, and washed and purified with anhydrous ethanol solution and dried (the washing and purification with anhydrous ethanol and drying were repeated three times), and the sample was dried and powdered to obtain a fluid loss reducer.

[0040] Drilling fluid: Add 300 mL of deionized water to a high-speed stirring cup, slowly add 7.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain the base slurry; then add 10 g of the above-mentioned fluid loss reducer, 12 g of sodium chloride and 6.5 g of sodium carbonate to the base slurry in sequence under stirring to obtain the drilling fluid.

[0041] Example 2

[0042] This embodiment provides a drilling fluid, and the preparation method thereof is as follows:

[0043] Polymer: Place a magnetic stirring bar in a four-necked flask, connect a thermometer and a condenser, fix the four-necked flask in a constant temperature heating magnetic stirrer, then dissolve 33.8 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in 373 g of deionized water, and adjust the pH of the system to 7 with a NaOH solution, then add 55.267 g of acrylamide (AM) and 12.267 g of sodium styrene sulfonate (SSS), stir well, introduce nitrogen for bubbling and deoxygenation for 1 hour until there is no oxygen in the four-necked flask and the solution, start heating to 40°C, add 0.3 g of initiator (the molar ratio of ammonium persulfate to potassium persulfate is 1:1), and carry out polymerization reaction at 40°C for 6 hours to obtain a polymer.

[0044] Fluid loss reducer: 0.5067 g of inorganic nano zinc oxide particles were added to 50 g of deionized water, and ultrasonically vibrated for 1 hour to obtain a uniformly dispersed nano silicon dioxide suspension; then the suspension was added dropwise to the above-mentioned four-necked flask containing the polymer, and after stirring at 40°C for 1 hour, the stirring was stopped and the temperature was raised to 60°C for aging for 1 hour until it became a gel; then the gel was cut into pieces and dried, and washed and purified with anhydrous ethanol solution and dried (the washing and purification with anhydrous ethanol and drying were repeated three times), and the sample was dried and powdered to obtain a fluid loss reducer.

[0045] Drilling fluid: Add 350 mL of deionized water to a high-speed stirring cup, slowly add 10.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain the base slurry; then add 12 g of the above-mentioned fluid loss reducer, 23.5 g of sodium chloride and 5 g of sodium carbonate to the base slurry in sequence under stirring to obtain the drilling fluid.

[0046] Example 3

[0047] This embodiment provides a drilling fluid, and the preparation method thereof is as follows:

[0048] Polymer: Place a magnetic stirring bar in a four-necked flask, connect a thermometer and a condenser, fix the four-necked flask in a constant temperature heating magnetic stirrer, then dissolve 45.78 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in 290 g of deionized water, and adjust the pH of the system to 6 with a NaOH solution, then add 125.67 g of acrylamide (AM) and 19.2 g of sodium styrene sulfonate (SSS), stir well, introduce nitrogen for bubbling and deoxygenation for 1 hour until there is no oxygen in the four-necked flask and the solution, start heating to 60°C, add 0.6 g of initiator (the molar ratio of ammonium persulfate to potassium persulfate is 1:1), and carry out polymerization reaction at 60°C for 4 hours to obtain a polymer.

[0049] Fluid loss reducer: Add 2.578g of inorganic nano-alumina particles into 50g of deionized water and ultrasonically vibrate for 1h to obtain a uniformly dispersed nano-silicon dioxide suspension; then add it dropwise into the above-mentioned four-necked flask containing the polymer, and stir at 60°C for 1h, then stop stirring and raise the temperature to 70°C for aging for 2 hours until it becomes a gel; then cut the gel into pieces and dry it, and wash and purify it with anhydrous ethanol solution and dry it (washing and purification with anhydrous ethanol and drying are repeated three times), dry the sample and grind it into powder to obtain a fluid loss reducer.

[0050] Drilling fluid: Add 400 mL of deionized water to a high-speed stirring cup, slowly add 15.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain the base slurry; then add 17 g of the above-mentioned filtrate reducer, 15 g of sodium chloride and 7.5 g of sodium carbonate to the base slurry in sequence under stirring to obtain the drilling fluid.

[0051] Example 4

[0052] This embodiment provides a drilling fluid, and the preparation method thereof is as follows:

[0053] Polymer: Place a magnetic stirring bar in a four-necked flask, connect a thermometer and a condenser, fix the four-necked flask in a constant temperature heating magnetic stirrer, then dissolve 50.7 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in 327 g of deionized water, and adjust the pH of the system to 8 with a NaOH solution, then add 99.34 g of acrylamide (AM) and 25 g of sodium styrene sulfonate (SSS), stir well, introduce nitrogen for bubbling and deoxygenation for 1 hour until there is no oxygen in the four-necked flask and the solution, start heating to 55°C, add 0.5 g of initiator (the molar ratio of ammonium persulfate to potassium persulfate is 1:1), and carry out polymerization reaction at 55°C for 5 hours to obtain a polymer.

[0054] Fluid loss reducer: 9.66 g of inorganic nano titanium dioxide particles were added to 50 g of deionized water, and ultrasonically oscillated for 1 hour to obtain a uniformly dispersed nano silicon dioxide suspension; then it was added dropwise into the above-mentioned four-necked flask containing the polymer, and after stirring at 55°C for 1 hour, the stirring was stopped and the temperature was raised to 65°C for aging for 1 hour until it became a gel; then the gel was cut into pieces and dried, and washed and purified with anhydrous ethanol solution and dried (the washing and purification with anhydrous ethanol and drying were repeated three times), and the sample was dried and powdered to obtain a fluid loss reducer.

[0055] Drilling fluid: Add 380 mL of deionized water to a high-speed stirring cup, slowly add 20.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain the base slurry; then add 8.0 g of the above-mentioned fluid loss reducer, 10 g of sodium chloride and 13 g of sodium carbonate to the base slurry in sequence under stirring to obtain the drilling fluid.

[0056] Example 5

[0057] This embodiment provides a drilling fluid, and the preparation method thereof is as follows:

[0058] Polymer: Place a magnetic stirring bar in a four-necked flask, connect a thermometer and a condenser, fix the four-necked flask in a constant temperature heating magnetic stirrer, then dissolve 50.7 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in 327 g of deionized water, and adjust the pH of the system to 8 with a NaOH solution, then add 110.2 g of acrylamide (AM) and 16.9 g of sodium styrene sulfonate (SSS), stir well, introduce nitrogen for bubbling and deoxygenation for 1 hour until there is no oxygen in the four-necked flask and the solution, start heating to 55°C, add 0.6 g of initiator (the molar ratio of ammonium persulfate to potassium persulfate is 1:1), and carry out polymerization reaction at 55°C for 5 hours to obtain a polymer.

[0059] Fluid loss reducer: 12.66 g of inorganic nano-silicon dioxide particles were added to 50 g of deionized water, and ultrasonically vibrated for 1 hour to obtain a uniformly dispersed nano-silicon dioxide suspension; then the suspension was added dropwise to the above-mentioned four-necked flask containing the polymer, and stirred at 55°C for 1 hour, then the stirring was stopped and the temperature was raised to 65°C for aging for 1 hour until it became a gel; then the gel was cut into pieces and dried, and washed and purified with anhydrous ethanol solution and dried (washing, purification and drying with anhydrous ethanol were repeated three times), and the sample was dried and powdered to obtain a fluid loss reducer.

[0060] Drilling fluid: Add 400 mL of deionized water to a high-speed stirring cup, slowly add 24.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain the base slurry; then add 18 g of the above-mentioned fluid loss reducer, 10 g of sodium chloride and 7 g of sodium carbonate to the base slurry in sequence under stirring to obtain the drilling fluid.

[0061] Example 6

[0062] This embodiment provides a drilling fluid, and the preparation method thereof is as follows:

[0063] Polymer: Place a magnetic stirring bar in a four-necked flask, connect a thermometer and a condenser, fix the four-necked flask in a constant temperature heating magnetic stirrer, then dissolve 50.7 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in 327 g of deionized water, and adjust the pH of the system to 8 with a NaOH solution, then add 123.4 g of acrylamide (AM) and 19.9 g of sodium styrene sulfonate (SSS), stir well, introduce nitrogen for bubbling and deoxygenation for 1 hour until there is no oxygen in the four-necked flask and the solution, start heating to 55°C, add 0.6 g of initiator (the molar ratio of ammonium persulfate to potassium persulfate is 1:1), and carry out polymerization reaction at 55°C for 5 hours to obtain a polymer.

[0064] Fluid loss reducer: 14.66 g of inorganic nano-silicon dioxide particles were added to 50 g of deionized water, and ultrasonically vibrated for 1 hour to obtain a uniformly dispersed nano-silicon dioxide suspension; then it was added dropwise into the above-mentioned four-necked flask containing the polymer, and after stirring at 55°C for 1 hour, the stirring was stopped and the temperature was raised to 65°C for aging for 1 hour until it became a gel; then the gel was cut into pieces and dried, and washed and purified with anhydrous ethanol solution and dried (the washing and purification with anhydrous ethanol and drying were repeated three times), and the sample was dried and powdered to obtain a fluid loss reducer.

[0065] Drilling fluid: Add 400 mL of deionized water to a high-speed stirring cup, slowly add 28.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain the base slurry; then add 13.275 g of the above-mentioned fluid loss reducer, 20 g of sodium chloride and 7 g of sodium carbonate to the base slurry in sequence under stirring to obtain the drilling fluid.

[0066] Comparative Example 1

[0067] The drilling fluid provided in this comparative example is similar to that in Example 5, except that the order of adding the inorganic nano-material silicon dioxide is different. The preparation method of the drilling fluid provided in this comparative example is as follows:

[0068] Polymer: Place a magnetic stirrer in a four-necked flask, connect a thermometer and a condenser, fix the four-necked flask in a constant temperature heating magnetic stirrer, then dissolve 50.7 g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in 327 g of deionized water, and adjust the pH of the system to 8 with a NaOH solution, then add 110.2 g of acrylamide (AM), 16.9 g of sodium styrene sulfonate (SSS) and 12.66 g of inorganic nano-silica, stir well, introduce nitrogen for bubbling and deoxygenation for 1 hour until there is no oxygen in the four-necked flask and the solution, start heating to 55°C, add 0.6 g of initiator (the molar ratio of ammonium persulfate to potassium persulfate is 1:1), and carry out polymerization reaction at 55°C for 5 hours to obtain a polymer.

[0069] Fluid loss reducer: The polymer synthesized above is heated to 65°C and aged for 1 hour until it becomes a gel; the gel is then cut into pieces and dried, and washed and purified with anhydrous ethanol solution and dried (the washing and purification with anhydrous ethanol and drying are repeated three times), and the sample is dried and powdered to obtain a fluid loss reducer.

[0070] Drilling fluid: Add 400 mL of deionized water to a high-speed stirring cup, slowly add 24.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain the base slurry; then add 18 g of the above-mentioned fluid loss reducer, 10 g of sodium chloride and 7 g of sodium carbonate to the base slurry in sequence under stirring to obtain the drilling fluid.

[0071] Comparative Example 2

[0072] The drilling fluid provided in this comparative example is similar to that in Example 5, except that acrylic acid is used instead of 2-acrylamido-2-methylpropanesulfonic acid in this comparative example. The preparation method of the drilling fluid provided in this comparative example is as follows:

[0073] Polymer: Place a magnetic stirring bar in a four-necked flask, connect a thermometer and a condenser, fix the four-necked flask in a constant temperature heating magnetic stirrer, then dissolve 17.6 g of acrylic acid in 327 g of deionized water, and adjust the pH of the system to 8 with a NaOH solution, then add 110.2 g of acrylamide (AM) and 16.9 g of sodium styrene sulfonate (SSS), stir well, introduce nitrogen for bubbling and deoxygenation for 1 hour until there is no oxygen in the four-necked flask and the solution, start heating to 55°C, add 0.6 g of initiator (the molar ratio of ammonium persulfate to potassium persulfate is 1:1), and carry out polymerization reaction at 55°C for 5 hours to obtain a polymer.

[0074] Fluid loss reducer: 12.66 g of inorganic nano-silicon dioxide particles were added to 50 g of deionized water, and ultrasonically vibrated for 1 hour to obtain a uniformly dispersed nano-silicon dioxide suspension; then the suspension was added dropwise to the above-mentioned four-necked flask containing the polymer, and stirred at 55°C for 1 hour, then the stirring was stopped and the temperature was raised to 65°C for aging for 1 hour until it became a gel; then the gel was cut into pieces and dried, and washed and purified with anhydrous ethanol solution and dried (washing, purification and drying with anhydrous ethanol were repeated three times), and the sample was dried and powdered to obtain a fluid loss reducer.

[0075] Drilling fluid: Add 400 mL of deionized water to a high-speed stirring cup, slowly add 24.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain the base slurry; then add 18 g of the above-mentioned fluid loss reducer, 10 g of sodium chloride and 7 g of sodium carbonate to the base slurry in sequence under stirring to obtain the drilling fluid.

[0076] Comparative Example 3

[0077] This comparative example provides a method for preparing a drilling fluid, comprising the following steps:

[0078] Add 300 mL of deionized water to a high-speed stirring cup, slowly add 7.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and the blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain a base slurry; then add 10 g of the polymer prepared in Example 1, 12 g of sodium chloride and 6.5 g of sodium carbonate to the base slurry in sequence under stirring to obtain a drilling fluid.

[0079] Comparative Example 4

[0080] The drilling fluid provided in this comparative example is similar to that in Example 1, except that the amount of the polymerized monomer used in the polymer preparation process is different. The preparation method of the drilling fluid provided in this comparative example comprises the following steps:

[0081] Polymer: Place a magnetic stirrer in a four-necked flask, connect a thermometer and a condenser, fix the four-necked flask in a constant temperature heating magnetic stirrer, dissolve 25.35g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in 327g of deionized water, adjust the pH of the solution to 8 with a NaOH solution, add 106.2g of acrylamide (AM) and 8.45g of sodium styrene sulfonate (SSS), and stir well; then introduce nitrogen into the solution, bubbling and deoxygenating for 1h until there is no oxygen in the four-necked flask and the solution. Start heating to 55°C, add 0.42g of initiator (the molar ratio of ammonium persulfate to potassium persulfate is 1:1), react at 55°C for 5h to obtain a polymer;

[0082] Fluid loss reducer: Add 4.66g of inorganic nano-silicon dioxide particles to 50g of deionized water, and ultrasonically vibrate for 1h to obtain a suspension; then drop the suspension into the above-mentioned four-necked flask containing the polymer, stir at 55℃ for 1h, stop stirring and heat to 65℃, and age for 1h to become a gel. Cut the gel into pieces and dry them, and then wash, purify and dry them with anhydrous ethanol solution, and repeat three times. Then dry the sample and grind it into powder to obtain a fluid loss reducer.

[0083] Drilling fluid: Add 300 mL of deionized water to a high-speed stirring cup, slowly add 7.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain the base slurry; then add 10 g of the above-mentioned fluid loss reducer, 12 g of sodium chloride and 6.5 g of sodium carbonate to the base slurry in sequence under stirring to obtain the drilling fluid.

[0084] Comparative Example 5

[0085] The drilling fluid provided in this comparative example is similar to that in Example 1, except that the amount of the polymerized monomer used in the polymer preparation process is different. The preparation method of the drilling fluid provided in this comparative example comprises the following steps:

[0086] Polymer: Place a magnetic stirrer in a four-necked flask, connect a thermometer and a condenser, fix the four-necked flask in a constant temperature heating magnetic stirrer, dissolve 33.8g of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) in 327g of deionized water, adjust the solution pH to 8 with NaOH solution, add 94.93g of acrylamide (AM) and 11.27g of sodium styrene sulfonate (SSS), and stir well. Then, introduce nitrogen into the solution, and bubble and deoxygenate for 1 to 2 hours until there is no oxygen in the four-necked flask and the solution, then start to heat up to 55°C, add 0.42g of initiator (the molar ratio of ammonium persulfate to potassium persulfate is 1:1), and react for 5 hours to obtain a polymer.

[0087] Fluid loss reducer: Add 4.66g of inorganic nano-silicon dioxide particles to 50g of deionized water, and ultrasonically vibrate for 1h to obtain a suspension; add the suspension dropwise into the above-mentioned four-necked flask containing the polymer, and stir at 55℃ for 1h. Stop stirring and heat to 65℃, and age for 1 hour to become a gel. Cut the gel into pieces and dry it, and then wash, purify and dry it with anhydrous ethanol solution, and repeat three times. Then dry the sample and grind it into powder to obtain a fluid loss reducer.

[0088] Drilling fluid: Add 300 mL of deionized water to a high-speed stirring cup, slowly add 7.0 g of sodium bentonite while stirring, and stir at high speed for 20 minutes, stopping twice during the period (the purpose is to add the clay on the cup wall and blades into the base slurry), and then close and cure at 24°C ± 3°C for 24 hours to obtain the base slurry; then add 10 g of the above-mentioned fluid loss reducer, 12 g of sodium chloride and 6.5 g of sodium carbonate to the base slurry in sequence under stirring to obtain the drilling fluid.

[0089] Performance Testing

[0090] The drilling fluids prepared in the above-mentioned embodiments and comparative examples were heated at 220°C for 16 hours according to the drilling fluid industry standard: SY-T5621-93 "Drilling Fluid Test Procedure", and then the medium-pressure filtration loss was measured using a high-temperature filtration tester. The specific test results are shown in the following table.

[0091] Table 2

[0092]

[0093] From the data of Examples 1 to 6 in the above table, it can be seen that the content of the fluid loss reducer in the drilling fluid provided by the present invention is between 1.5wt% and 4wt%, and the medium pressure fluid loss after hot rolling at 220°C for 16h is ≤20mL. This indicates that the fluid loss reducer provided by the present invention can meet the requirements of 220°C ultra-high temperature oil reservoirs.

[0094] From the data of Comparative Example 1, it can be seen that the content of the fluid loss reducer in Comparative Example 1 in the drilling fluid is 4wt%, and the medium-pressure fluid loss after hot rolling at 220°C for 16h is 93mL, which cannot meet the requirements of ultra-high temperature oil reservoirs at 220°C. Since the silanol groups on the surface of the inorganic nano-silica material and the polar groups of the polymerized monomers are adsorbed each other, physical isolation is generated between the polymerized monomers, and the number of large side chain groups grafted with rigid benzene ring groups is reduced, and the ultra-high temperature resistance effect cannot be achieved.

[0095] The data of comparative example 2 show that the medium pressure filtration loss after hot rolling at 220°C for 16 hours is 159 mL. Since the monomer 2-acrylamide-2-methylpropanesulfonic acid (AMPS) is replaced with acrylic acid, the large side chain groups in the filtrate reducer polymer are reduced and the temperature resistance is reduced.

[0096] From the data of comparison ratio 3, it can be seen that the filtrate reducer in the drilling fluid adopts the polymer prepared in Example 1, and no inorganic nano-silicon dioxide particles are added. The medium-pressure filtration loss after hot rolling at 220°C for 16 hours is 144 mL, which cannot meet the requirements of ultra-high temperature oil reservoirs at 220°C. Not adding inorganic nano-silicon dioxide particles has no obvious effect on the drilling fluid system and cannot play a role in reducing filtration loss.

[0097] However, the medium-pressure filtration loss of the drilling fluids prepared in Comparative Examples 4 and 5 after hot rolling at 220°C for 16 hours was 121 and 92 mL, respectively, indicating that after adjusting the dosage ratio of each monomer, the obtained filtration loss reducer could not meet the demand of 220°C high-temperature oil reservoirs.

[0098] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a fluid loss reducer, characterized in that: The steps include: The 2-acrylamido-2-methylpropanesulfonic acid solution is adjusted to be neutral, mixed with acrylamide and sodium styrene sulfonate, and then polymerized in an oxygen-free atmosphere and under the action of an initiator to obtain a polymer; adding a uniformly dispersed nanomaterial suspension to the polymer, aging to form a gel, crushing, drying, washing, drying again, and crushing again to obtain the fluid loss reducer; Among them, the molar ratio of the 2-acrylamide-2-methylpropane sulfonic acid to the acrylamide is 1:(4-8), the molar ratio of the 2-acrylamide-2-methylpropane sulfonic acid to the sodium styrene sulfonate is (2-3):1, and the molar ratio of the 2-acrylamide-2-methylpropane sulfonic acid to the nanomaterial is 1:(0.01-1).

2. The preparation method according to claim 1, characterized in that The nano material is selected from any one of nano calcium carbonate, nano silicon dioxide, nano aluminum oxide, nano magnesium carbonate, nano zinc oxide and nano titanium oxide; nano silicon dioxide is preferred.

3. The preparation method according to claim 1, characterized in that: The initiator is selected from ammonium persulfate and / or potassium persulfate.

4. The preparation method according to claim 1, characterized in that: The polymerization reaction temperature is 40-60° C. and the reaction time is 4-6 hours.

5. The preparation method according to claim 1, characterized in that: The temperature of the uniformly dispersed nano material suspension when added to the polymer is 40-60°C.

6. The preparation method according to claim 1, characterized in that: The aging temperature is 60-70°C.

7. A fluid loss reducer, characterized in that: The fluid loss reducer is prepared by the preparation method of any one of claims 1 to 6.

8. A water-based drilling fluid, characterized in that: A fluid loss reducer prepared by the preparation method of the fluid loss reducer according to any one of claims 1 to 6; based on the total mass of the water-based drilling fluid being 100%, the content of the fluid loss reducer is 1.5wt% to 4wt%.

9. The water-based drilling fluid according to claim 8, characterized in that: The water-based drilling fluid also includes bentonite, sodium chloride and sodium carbonate; preferably, based on the total mass of the water-based drilling fluid as 100%, the content of the bentonite is 2% to 6%, the content of the sodium chloride is 2% to 6%, and the content of the sodium carbonate is 1% to 3%.

10. Use of the water-based drilling fluid according to claim 8 or 9 in oil and gas drilling.

Citation Information

Patent Citations

  • A high-temperature resistant, high-calcium salt drilling fluid and its preparation method

    CN108424754B

  • Low-viscosity copolymer filtrate loss reducer for drilling fluid and preparation method of low-viscosity copolymer filtrate loss reducer

    CN108467713A

  • A calcium-resistant and high-temperature-resistant drilling fluid filtration reducer and its preparation method

    CN109554170B

Cited By

  • Anti-calcium nano-porous filtrate reducer for water-based drilling fluid and preparation method of anti-calcium nano-porous filtrate reducer

    CN121045447A